Presenting a Model of Strategies Influencing School Social Responsibility with Emphasis on Student Participation in School Activities - Noori, Mahmood; Nami, Kolsum; Bagheri, Mehdi (Assessment and Practice in Educational Sciences, 2025)
The present study aims to develop a model of strategies influencing students’ social responsibility with a particular emphasis on their participation in school activities. This study is an applied research project using a quantitative approach. The statistical population included all teachers and students in the city of Larestan. Stratified random sampling was employed, and based on Morgan’s table, 357 students and 181 teachers were selected as the sample. Data collection was carried out using a researcher-developed questionnaire, which was constructed based on initial qualitative findings and evaluated using a five-point Likert scale. Data analysis was performed using SPSS and PLS software. The results of the measurement model analysis showed that all factor loadings were above 0.40 and all t-values were greater than 1.96, indicating the significance of the relationships between items and constructs at the 95% confidence level. Additionally, composite reliability, Cronbach’s alpha, and convergent validity for all dimensions exceeded the acceptable thresholds. The final conceptual model included components such as delegation of authority, trust in students, the role of the family, reinforcement of leadership traits, and encouragement of responsibility—all of which had significant effects in explaining social responsibility. The findings indicated that genuine student participation in school affairs and the creation of democratic environments play a key role in enhancing their social responsibility. The model proposed in this study can serve as a foundation for designing educational policies based on participation, trust, and effective citizenship education.